POSHAN’s abstract digest on maternal and child nutrition research - Issue 44 - Avula, Rasmi (International Food Policy Research Institute, 2022)
Issue 44 of the POSHAN Abstract Digest, brings to you yet another collection of articles on various topics pertaining to maternal and child nutrition. This issue features several studies on the nutritional status of adolescents and the relationship between maternal dietary diversity and body composition with children’s health. A few studies look at coverage of nutrition and health interventions in the country, including the Anemia Mukt Bharat program and the National Rural Health mission.